Development of Balinese Customary Law in the Perspective of Local Wisdom “Tri Hita Karana’’ - Nyoman Gede Antaguna; I Nyoman Putu Budiartha (Sociological Jurisprudence Journal, 2023)
This research article explores the development of Balinese Customary Law within the context of the profound local wisdom known as "Tri Hita Karana." The study delves into the distinctive features of customary law in Bali and its evolution in the contemporary era. This article aim is to describe regarding customary law in Bali and how it develops in the modern era. Its unique raises some discussion for some jurist and academic community, how the legal sytem works in the dominate of costomary law in Bali. This article also trying to identified what is insist in Bali’s customary Law. Bali is a very popular tourism destination in the world. The arrival of millions foreign tourists per year with diverse backgrounds. The presence of these foreign has created a cross of cultures in the society, furthermore with advances in science and technology. Over the years those phenomena happened in Bali. Nevertheless, Balinese culture is very strongly applied by its citizens. The activities of religious ceremonies, arts and customs are very strong as daily activities. This is what is unique to Bali in the perception of the world, not solely because of the beauty of its panorama. Customary Law is still applied in Bali which binds the community in addition to the applicable Positive Law. Recognition of this customary legal entity is accommodated in several forms of legislation. Each indigenous community, referred to as an Indigenous Village, has its own customary laws. They are the ones who compile customary laws that have implications for the respect of their society for the customs in Bali. Enriched by Balinese local wisdom, notably the revered philosophy of "Tri Hita Karana," Customary Law stands as a cornerstone of the island's legal and cultural identity.